Evaluation of sweet taste sensitivity in type-II Diabetes Mellitus patients - Kumar, Z. Naveen; Kumari, B.N.S. Gowri (International Journal of Clinical and Biomedical Research, 2020)
Background: The objective is to evaluate the sweet taste sensitivity among type-II diabetes mellitus patients. Methods: This is a cross sectional study consisted of 227 subjects (127 type-II Diabetic patients & 100 non diabetic individuals) of both the genders and age matched. Sweet taste sensitivity tests were done using different concentrations of glucose solution and compared among the diabetic patients with FBS more than 180mg/dl and diabetic patients with FBS less than 180mg/dl and also compared among the diabetic patients and non diabetic individuals. The final concentration at which patient was able to perceive the taste was recorded. statistical analysis was done using Student’s unpaired T test. Pvalues of < 0.05 were considered to be statistically significant. Results: The mean of sweet taste sensitivity among diabetic patients with FBS >180 mg/dl was 6245 mg/l and the mean of sweet taste sensitivity in the diabetic patients with FBS <180 mg/dl was 2249mg/l with P<0.001 which is significant. The mean of sweet taste sensitivity among diabetic patients with FBS >180 mg/dl was 6245mg/l and the mean of sweet taste sensitivity in the non diabetic individuals was 1979mg/l with P<0.01 which is significant. the mean of sweet taste sensitivity among diabetic patients with FBS <180 mg/dl was 2249 mg/l and the mean of sweet taste sensitivity in the non diabetic individuals was 1979mg/l with P>0.05 which is not significant. Conclusion: In our study it was concluded that type-II Diabetes Mellitus patients have lesser sensitivity for the sweet taste. Loss of sensitivity leads to the increase in sugar consumption being the risk factor for worsening the disease.